KEEFEKTIFAN PENGGUNAAN MEDIA PAPAN CERITA DALAM PEMBELAJARAN MENULIS TEKS FABEL PADA KELAS VII MTS YAPI PAKEM SLEMAN YOGYAKARTA TAHUN PELAJARAN - Hartutik Sulistyo Wati; Wijaya Heru Santosa (CARAKA, 2019)
The purpose of this research is to describe of writing ability fable story text made by 7Th grade students of MTs YAPI Pakem and to prove positive and significant trend between writing ability of fable text using storyboard media made by 7Th grade students of MTs YAPI Pakem. This research was used random samping technique which is class A is an experiment class and class B is a control class. The collection of data uses the objective test and the triangulation test. The instrument validity is content validity with expert judgment. The result from alpha Cronbach technique is 0.843 so this instrument is reliable. The result of the research shows the preferences writing ability of fable text with storyboard media is very high category on the average 76,5. The ability to write fable text with the print media is a high category on the average 71,38. In comparative from Â 3,087 that is >Â 1,672 so that can conluded that there are significant differences from user storyboard media toward write of fable text in the 7Th grade students of MTs YAPI Pakem.